Measurement of absolute branching fractions of inclusive semileptonic decays of charm and charmed-strange mesons - Asner, D; Edwards, K; Reed, J; Robichaud, A; Tatishvili, G; White, E; Briere, R; Vogel, H; Onyisi, P; Rosner, J; Alexander, J; Cassel, D; et al. (2010)
We have measured the inclusive semileptonic branching fractions of D0, D+, and Ds+ mesons. For these measurements, we have used the full CLEO-c open-charm data samples, 818pb-1 at ECM=3.774GeV, giving D0D̄0 and D+D- events, and 602pb -1 at ECM=4.170GeV, giving Ds*±Ds" events. We obtain B(D0→Xe+νe)=(6.46±0.09±0.11)%, B(D +→Xe+νe)=(16.13±0.10±0.29)%, and B(Ds+→Xe+νe)=(6.52±0.39±0.15)%, where the first uncertainties are statistical and the second are systematic. From these and lifetimes obtained elsewhere, we obtain the ratios of semileptonic decay widths Γ(D+→Xe+νe)/Γ(D0→Xe +νe)=0.985±0.015±0.024 and Γ(Ds+→Xe +νe)/Γ(D0→Xe+νe)=0.828±0. 051±0.025. The ratio of D+ and D0 is consistent with the isospin symmetry prediction of unity, and the ratio of Ds+ and D0 differs from unity, as expected. © 2010 The American Physical Society.